(3GdGfJaGVI GdeHGQcI heSJbHdgG (B/s - (3LgGO, LgGO eMeOs ((3GdchjJ (B:s (3ecJHI GdadGM ddfTQ hGdJhRjY,s, 1988)
(3jJfGhd cJGH (B((3GdEfJaGVI GdeHGQcI heSJbHdgG(B) (3hGdPj bGe HJCdjag LgGO eMeO LgGO, ehVhY (B((3GdEfJaGVI GdeHGQcI(B) (3GdcJGH YQV eNJUQ hJSLjd Ydi YLd dHQcGf GfJaGVI GdTYH GdadSWjfj GdefOdYI ef OjSeHQ YGe (B1987(3e(B. (3dbO cGfJ gPg GdEfJaGVI GdeHGQcI fhQG CVGA ddLjd WQjbG, HYO Cf COdge Gddjd hQGgf GdYOh Ydi VYag hYLRg(B. (3hHYO Cf jFS GdcKjQhf ef Whd GdOQH hcKQI GdCThGc hJOab GdOeGA hYeb GdLQGM(B. (3MjK cGfJ gPg GdEfJaGVI eaGLCI de jJhbYgG GdYGde, hXf GdcKjQhf CfgG fRhI THGH WGFT, aEPG gj bjGOI LgGOjI MbjbjI UGeOI hGYjI, hXfhG CfgG dG JSJWjY Cf Jba aj hLg GdeMJd GdeOLL HGdSdGM, aEPG gj RdRGd JMJ CbOGe LfhO GdYOh(B. s
Keywords: (3GdGfJaGVI GdadSWjfjI, (B1987-1993s; (3adSWjfs -- (3JGQjNs -- (3GfJaGVI GdCbUi, (B1987-1993s